INTERDISCIPLINARY RELATIONS AND CURRICULAR STRATEGIES IN THE HUMANIST FORMATION OF THE CUBAN PROFESSIONAL OF EDUCATION. AN EXPERIENCE IN THE MARXISM-LENINISM AND HISTORY SPECIALTY - Jiménez Sánchez, Lissette (Atenas, 2014)
The paper centers its attention on revealing the didactic connections and articulations which can be established in the interdisciplinary process, pertinent as it is for the formation of Cuban professionals of education, and the curricular strategies, facilitators of the materialization of the aspirations in the teacher training process in Cuba. The theoretical systematization goes along with a practical demonstration in a particular career: Marxism-Leninism and History.